Metal Phosphides: Preparation, Characterization and Catalytic Reactivity - Prins, Roel; Bussell, Mark E. (Catalysis letters, 2012)
The preparation, characterization, and catalytic activity of supported metal phosphides are reviewed. Reduction of metal compounds together with phosphate is a convenient method to prepare metal phosphides, but requires high temperature. Reduction with phosphite, hypophosphite, or phosphine and the plasma reduction of phosphate can be carried out at lower temperatures, which leads to smaller metal phosphide particles and more active catalysts. Organometallic routes allow the separate synthesis of metal phosphide nanoparticles, which have to be added to the support in a second step. LEED, STM, XPS, and DFT studies have shown that the surfaces of Ni 2 P reconstruct to P-rich surfaces. The investigation of metal phosphides as catalysts for hydrotreating reactions continues to be a topic of considerable research with recent advances realized in using bimetallic and noble metal phosphides to achieve high activities and tailored selectivities. Finally, hydrodeoxygenation catalysis over metal phosphides is a growing area of research given the need to develop catalysts for upgrading biomass to transportation fuels. Graphical Abstract